(untitled) - Thayer, George (New York, 1973)
This book tells the side of political campaigns that goes largely unseen by the voting public. This writing takes you well into the world of campaign fundraising. You are told who donates campaign funds to the Democrats as well as the Republicans. You are also told how many of these campaign funds are utilized by each political party. Another very interesting section of this book is the role of the political consultant(campaign manager) in the elections of today. Several of the more sucessful political consultants are highlighted. This writing gives you very good insight into the world of elections. Read this book and you will be entertained and gain knowledge as well.
Keywords: Campaign funds,Quỹ cuộc vận động; History; United States